Substitutional effect of Ni-Al in electromagnetic properties of Sr-hexaferrite based non-rare earth magnet with high energy density for motor applications - Gupta A.; Kar M.; Roy P.K. (My University, 2025)
Strontium hexaferrite is a hard magnet that can help to develop rare-earth-free magnets for permanent magnet applications. A composition of SrFe12-x-yNixAlyO19 (0.005 ≤ x ≤ 0.02; 1 ≤ y ≤ 4) is successfully synthesized with by the sol-gel auto-combustion process, and the effect of Ni-Al substitution is studied on the structural, magnetic, dielectric, and electrical properties. The XRD analysis confirms the formation of magnetoplumbite hexagonal structure with P63/mmc space group. Magnetic studies have shown a massive improvement in the coercivity (Hc) of the samples. The highest ever Hc value of 24.44 kOe in strontium hexaferrite-based rare-earth free magnet is attained for the SrFe7.98Ni0.02Al4O19 ferrite composition. The energy density (BH)max is effectively tuned to 16.2 MGOe for the SrFe8.985Ni0.015Al3O19 composition. The dielectric properties have shown the typical behavior of ferrites and are explained according to the Maxwell-Wagner and Koop model. The proposed work is expected to offer an immense possibility to improve the hard magnetic properties of strontium hexaferrite magnets comparable to the expensive NdFeB magnets in order to fully/partially replace them in different permanent magnet applications. © 2022 Elsevier B.V.